The Prevalence of Osteoporosis in the Thrace Region of Turkey: A Community-Based Study - AKYÜZ, GÜLSEREN DERYA; ÇEKİN, MURAT DİNÇER; LÜLECİ, NİMET EMEL; GÜNDÜZ, OSMAN HAKAN; KESKİN, YAŞAR (AVES, 2014)
Objective: This study was planned as a community-based research study to estimate the prevalence of osteoporosis and explore related risk factors in the Thrace region of Turkey. Material and Methods: The community-based study involved a total of 620 people, 498 women and 122 men, aged between 40 and 89 years. A questionnaire on the medical history and lifestyles of the participants was applied with a face-to-face interview. Body weight height, and arm span of each participant were measured, together with bone mineral density at the middle phalanges of the second, third, and fourth digits of the non-dominant hand using dual-energy X-ray laser absorptiometry. Results: Age, clothing, lack of regular exercise, and giving birth to more than two children seem to contribute to osteoporosis, while high education, high economic level, tea and moderate alcohol consumption, oral contraceptive use, and hormone replacement therapy seem to retard osteoporosis. Osteoporotic patients had more fractures in the past. Height and weight were significantly lower in osteoporotic women. Conclusion: Lifestyle affects the prevalence of osteoporosis. Drinking tea and alcohol seems to be controversial with regard to osteoporosis risk.
Keywords: Osteoporosis; bone density; risk factors; lifestyle; BONE-MINERAL DENSITY; CIGARETTE-SMOKING; RISK-FACTORS; POSTMENOPAUSAL WOMEN; HIP FRACTURE; CAFFEINE CONSUMPTION; TURKISH WOMEN; TEA DRINKING; OLDER WOMEN; MEN